Bergamottin (Ber) ameliorates the progression of osteoarthritis via the Sirt1/NF-κB pathway - Shen, Guangjie; Zhang, Weihao; Tu, Qiming; Wang, Juncheng (Frontiers in Pharmacology, 2024)
Osteoarthritis (OA) is a common chronic disease characterized by progressive cartilage degeneration and secondary synovial inflammation. Bergamottin(Ber) is an important natural derivative of the furanocoumarin compound, extracted from natural foods, such as the pulp of grapefruits and pomelos. Ber exhibits several characteristicsthat are beneficial to human health, such as anti-inflammation, antioxidant, and anti-cancer effects. However, the role of Ber in the treatment of OA has not been elucidated to date. Therefore, in the present study, in vitro experiments were conducted, which demonstrated that Ber reduces the secretion of inducible nitric oxide synthase (iNOS), nitric oxide (NO), cyclooxygenase-2 (COX2), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and prostaglandin E2 (PGE2) under the stimulation of interleukin-1β (IL-1β). Ber also reversed the IL-1 β-mediated aggrecan and type II collagen degradation within the extracellular matrix (ECM). In addition, in vivo experiments were conducted, in which Ber ameliorated the progression of OA in mice. It was revealed that Ber exerted its cellular effect by activating the Sirt1/NF-kB pathways. In conclusion, the present study demonstrated the therapeutic potential of Ber in the context of OA.